Breastfeeding, complementary feeding and supplementation multimicronutrient: intercultural perspective - Jessica Paola Bustamante Llatas; Miguel Amberly Gordillo Julón; Rosa Jeuna Díaz Manchay; Flor de María Mogollón Torres; Angelica Soledad Vega Ramírez; Sonia Tejada Muñoz (Universidad de Alicante, 2019)
Introduction: Feeding the child is essential for proper growth and healthy development; however some entrenched cultural practices in different communities have influenced the morbidity and infant mortality, despite health education provided by health personnel. Objective: To describe and understand breastfeeding, complementary feeding and supplementation multimicronutrient to lower infant from a cultural perspective. Method: A qualitative study, with ethnographic design. The sample consisted of 25 participants (10 nurses and 15 Andean mothers), chosen for convenience and determined by saturation technique and redundancy. For data collection ethnographic interview and participant observation was used, recorded in the diary, processed using thematic analysis. The criteria of scientific rigor and principles of personalistic bioethics was taken into account. Results: Emerged three cultural themes: A) Health education, customs and breastfeeding. B) Health education and cultural practices in complementary feeding. C) Health Education, and rejection multimicronutrient consumption. Conclusions: Health personnel educates the Andean mother about proper nutrition to be performed at home, but more prevalent customs and beliefs, which may result in poor growth and development.